MARKERS OF MYOCARDIAL DYSFUNCTION: THEIR ROLE IN THE PATHOGENESIS OF FUNCTIONAL DISORDERS OF THE CARDIOVASCULAR SYSTEM IN NEWBORNS - Перижняк, Алла; Юрков, Оксана (SWorldJournal, 2021)
The article is devoted to the establishment of the role of indicators of the biochemical spectrum of blood, a complex of indicators of the system of free radical oxidation and antioxidant defense of the body in the development of the pathogenesis of hypo